2015
DOI: 10.1186/s13099-015-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome architecture of Lactobacillus plantarum PS128, a probiotic strain with potential immunomodulatory activity

Abstract: BackgroundClinical and preclinical observations indicate that Lactobacillus plantarum has anti-inflammatory activity and may regulate the immune responses of its hosts when ingested. Recently, modification of teichoic acids (TAs) produced by L. plantarum was reported as a key to regulating the systemic immune response in mice. However, data linking TA-related genetic determinants and the immunomodulatory effect are limited. To provide genomic information for elucidating the underlying mechanism of immunomodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…DSM 28632. The genome architecture of PS128 was reported previously [61]. In the present study, the PS128 product was provided by Bened Biomedical Co., Ltd. in the final form of capsules containing creamy white powders.…”
Section: Methodsmentioning
confidence: 88%
“…DSM 28632. The genome architecture of PS128 was reported previously [61]. In the present study, the PS128 product was provided by Bened Biomedical Co., Ltd. in the final form of capsules containing creamy white powders.…”
Section: Methodsmentioning
confidence: 88%
“…Beneficial effects of PS128 TM on children with autism spectrum disorder (26), triathletes (27), and patients with major depressive disorder (28) have also been reported. PS128 TM may exert its psychotropic effects by altering monoamine neurotransmitter levels (22)(23)(24)(25), and modulating glucocorticoid (22), antiinflammatory, and anti-oxidative responses (21,22,27); however, the underlying mechanisms warrant further investigation. Despite the increase in the number of IT employees, the importance of the IT industry to the economy, and the high stress due to uncertainty and workload under time pressure, no study to date has investigated whether probiotics could help alleviate stress, sleep, or mood symptoms in highly stressed IT specialists.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Lactobacillus plantarum PS128 TM (PS128 TM ), isolated from spontaneously fermented mustard greens in Taiwan ( 21 ), has been demonstrated to reduce anxiety- and depression-like behaviors ( 22 , 23 ), ameliorate tic-like behaviors ( 24 ), and improve visceral hypersensitivity ( 25 ) in experimental animals. Beneficial effects of PS128 TM on children with autism spectrum disorder ( 26 ), triathletes ( 27 ), and patients with major depressive disorder ( 28 ) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, L. reuteri ameliorated the impaired social behavior observed in ASD animal models [ 46 , 47 ]. Anxiety- and depression-like behaviors observed in early life stressed (ELS) animals were recovered by the treatment of L. plantarum PS128, which reduced inflammation and corticosterone and increased dopamine and serotonin [ 113 , 114 ]. Another study reported that behavioral changes induced by chronic restraint stress were rescued by L. helveticus NS8, which increased serotonin and BDNF in the hippocampus [ 115 ].…”
Section: Probiotics For the Prevention Or The Treatment Of Mental Dismentioning
confidence: 99%